Learning Leadership from Donald Trump: What Not to Do - Friedman, Hershey H.; Fireworker, Robert B. (Journal of Leadership, Accountability and Ethics, 2019)
Donald Trump has served as President of the United States for more than two years. His performance in office has provided many valuable lessons about leadership, especially about what not to do. This paper offers a partial list of leadership principles one can deduce from observing his leadership style. In addition, actual Trump quotations are provided.